2017
DOI: 10.4236/ojog.2017.712123
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Plasma Lipid Profile in Women Screened for Gestational Diabetes Mellitus (GDM)

Abstract: Objective: This is to determine the plasma lipid profile status of patients diagnosed with gestational diabetes mellitus. Methodology: Seventy-nine pregnant women between gestational age of 24 and 28 weeks out of which 23 and 16 were diagnosed of having GDM using IADAPSG and WHO guidelines respectively were recruited into the study. Plasma lipid profile was determined among the study groups using standard laboratory techniques. Results: Higher numbers of women were diagnosed with GDM using IASDAPG criteria tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
0
1
2
Order By: Relevance
“…These findings are consistent with the results of a previous hospital-based study that showed significant differences in lipid parameters between the two groups ( p < 0.05) ( 21 ). However, our results contradict those of a previous study from Nigeria, which found no significant association between lipid profiles and GDM status ( 22 ).…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are consistent with the results of a previous hospital-based study that showed significant differences in lipid parameters between the two groups ( p < 0.05) ( 21 ). However, our results contradict those of a previous study from Nigeria, which found no significant association between lipid profiles and GDM status ( 22 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Hiperlipidemia biasanya terdeteksi pada paruh kedua kehamilan, yang dianggap sebagai mekanisme fisiologis yang diperlukan untuk menyediakan bahan bakar metabolik dan nutrisi bagi janin. Namun, masih belum jelas untuk memastikan tingkat elevasi lipid mana yang fisiologis atau patologis (Atiba et al, 2017;Hossain et al, 2020).…”
Section: Pendahuluanunclassified
“…Hiperlipidemia merupakan gambaran umum pada kehamilan normal dan terutama terdiri dari peningkatan trigliserida yang diikuti juga dengan peningkatan kolesterol total (Atiba et al, 2017;Vani, 2015). Metabolisme lipid yang menyimpang pada kehamilan normal ditandai dengan peningkatan dari kadar kolesterol total dan trigliserida sebagai akibat dari peningkatan sintesis hati dari trigliserida sebagai respon terhadap peningkatan kadar estrogen.…”
Section: Pembahasanunclassified